Impro visa Ação: uma proposta de treinamento para teatro de improviso - Proença, Luana Maftoum (2013)
Impro or Iprov is a theatrical form in which the show is created during its execution with the presence of the audience. Art Form directly influenced by the artistic and literary works of English director Keith Johnstone and the American director Viola Spolin, requires a specific skills training from the actor. This resheart is related to my experience as an actress in the Theatre-Sports show What Your Order? in Brasília-DF, connected with Impro s theorists, along with the Viewpoint s technique of the American directors Anne Bogart and Tina Landau, and the writings of the current coach of the Brazilian men\'s volleyball team, Bernardinho. For the work I planned and experimented a training system with the group Impro.Ato in Brasília. This group was formed by volunteers especially for this research. The parallel experience with the students of the Special Topics and Trends in Contemporary Theatre: Theatre-Sports and Improvisation class that I taught at the Uberlandia s Federal University in Minas Gerais, 2011. Those experiences contributed to the notes of experimentation with the Impro training to form an improvisator. The research s developments with my participation at the Intensive Classes of Second City Training Center at Chicago-IL, EUA, and the performance of the show named Red Line with the Impro.Ato, were also accurate for the reflections about the proposed training and its results.